Access to Information, Concerns, Myths and Truths on Food Safety During COVID-19: An Overview of Portuguese Population. (March 2022) - Lemos, M.; Maia, R.; Teixeira, P.
Abstract : Purpose: The COVID-19 pandemic raised questions and concerns about the possibility of transmission of SARS-CoV-2 via foods. While cases of COVID were rapidly rising, information related to the virus and ways of prevention was also increasing, with much of this information being provided by the media and the general population. In this context, this study had two main objectives: 1) To understand the doubts and concerns of the Portuguese population related to food safety during the first wave of COVID-19 and how they clarified these issues and 2) to analyze the population's opinion on myths and truths related to the transmission of the infection. Methods & Materials: A survey including questions about a) concerns and information on food safety during the first wave of COVID-19 pandemic; b) myths and truths about COVID-1 and c) respondents' profile. The survey was released online between June and October of 2020. Results: The main doubt of the respondents was related to the manipulation of food (40, 7%) followed by the possibility of transmission of COVID-19 through food (12, 6%) and which foods should be avoided due to the pandemic (12, 6%). 33, 3% of the participants stated that television was the main mean of information accessed to clarify these doubts, followed by a Guideline launched by the Directorate-General of Health (31, 8%). However, 50, 3% said that they had only found answers to some of their questions. 50% of the respondents with higher level of education and 30% of the respondents with lower level of education had doubts about the possibility of the transmission of COVID-19 through food. Also, most of the survey participants disagreed with the affirmations regarding popular ways of disinfecting food to prevent infection. Conclusion: COVID-19 pandemic raised several doubts, however when related to food safety, the main doubt was about the manipulation of food due to the concern of SARS-CoV-2 transmission. Most respondents do not believe myths about COVID-19 and food safety, but this was dependent on the level of education.